Digital Addiction and Body Balance: An Investigation of Postural Stability in Young Adults: A Cross‐Sectional Study. - Çırak, Yeliz; Güzel, Hüsna; Sert, Buse; Düşgün, Elif Sena; Yeşil, Büşra (Physiotherapy Research International, 2026)
Background and Purpose: Excessive use of digital devices has become increasingly common among young adults and has been associated with postural changes and impaired balance control. Since postural stability is essential for daily activities and musculoskeletal health, understanding the impact of digital addiction on balance is important for physiotherapy and rehabilitation. This study aimed to compare postural balance performance between young adults with and without smartphone addiction and to examine the effects of attention‐demanding tasks on balance control. Methods: This cross‐sectional study included a total of 74 volunteer students (mean age = 22.06 ± 6.66 years; 68.9% female, 31.1% male) from the Department of Therapy and Rehabilitation at Fenerbahçe University. Participants were classified into smartphone‐addicted and non‐addicted groups based on the Smartphone Addiction Scale–Short Version (SAS‐SV). Balance performance was assessed using the Becure Balance System under three conditions: eyes open, eyes closed, and texting. Results: Findings revealed that individuals with smartphone addiction (SA) exhibited significantly higher postural sway in the eyes‐open condition compared with non‐addicted individuals (p < 0.05). No significant differences were observed between groups under the eyes‐closed condition (p > 0.05). During the texting task, smartphone‐addicted individuals demonstrated lower postural sway values (p < 0.05). No significant differences were found between the groups in overall posture assessment. Discussion: The results indicate an association between smartphone addiction status and postural control during attention‐demanding tasks, suggesting that digital dependency may be related to differences in motor control and postural stability mechanisms in young adults. Future studies should include larger and more diverse samples, integrate dynamic balance assessments, and utilize objective postural analysis methods to further clarify the relationship between smartphone addiction and postural stability.